An analytic BRDF for materials with spherical Lambertian scatterers. (15th July 2021) - d'Eon, Eugene
Abstract: We present a new analytic BRDF for porous materials comprised of spherical Lambertian scatterers. The BRDF has a single parameter: the albedo of the Lambertian particles. The resulting appearance exhibits strong back scattering and saturation effects that height‐field‐based models such as Oren‐Nayar cannot reproduce.